Potentiodynamic dissolution study of PtRu/C electrocatalyst in the presence of methanol. (1st September 2016) - Jovanovič, Primož; Šelih, Vid Simon; Šala, Martin; Hočevar, Samo; Ruiz-Zepeda, Francisco; Hodnik, Nejc; Bele, Marjan; Gaberšček, Miran
Abstract: Dissolution of PtRu alloy nanoparticles on carbon support in acidic environment is qualitatively and quantitatively investigated using an advanced electrochemical technique: electrochemical flow cell (EFC) on-line coupled to inductively coupled plasma mass spectrometer (ICP-MS). Profound insights into potential-resolved corrosion stability of Ru-Pt alloy in the potential window from 0.05 to 1.6 V vs RHE are obtained. Compared to pure Pt the PtRu alloy is less stable due to destabilisation of Pt surface caused by Ru dissolution together with the presence of weaker Ru-Pt bonds. However, at high potentials (1.5 and 1.6 V) Pt gets stabilised, presumably via a Ru catalysed oxygen evolution reaction that acts as a cathodic protection. Both Ru and Pt dissolution are enhanced in the presence of methanol due to consumption of surface ruthenium oxides, presumably Ru2 O3, by the methanol oxidation reaction and an inhibited redeposition of Pt ions due to surface blockage of CO. The results may be used as useful guidelines in designing future DMFC and PEMFC catalysts.